1981
DOI: 10.1159/000468483
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cyclers and Antidepressants

Abstract: 434 bipolar manic-depressive patients were followed longitudinally. The course of the disease changed in many patients over the years. 67 cases became rapid cyclers (two or more cycles per year); in 40 of these cases (12 men and 28 women) the change of the course took place after intense or protracted use of antidepressant drugs. In their previous course these patients had not received antidepressant drugs. The common feature of the transformation of the previous course to a continuous circular one was the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…It has been suggested that there is a clinical link between rapid cycling and AIM. [9][10][11] The association that we observed between rapid cycling and the 5-HTTLPR may be related to the result obtained by Mundo et al Indeed, patients with rapid cycling may be over-represented among AIM(+) patients and under-represented among AIM(À) patients. Mundo et al only evaluated the presence of rapid cycling in the previous 12 months, whereas we considered the lifetime history of rapid cycling.…”
Section: -Htt Gene and Antidepressant-induced Maniasupporting
confidence: 61%
“…It has been suggested that there is a clinical link between rapid cycling and AIM. [9][10][11] The association that we observed between rapid cycling and the 5-HTTLPR may be related to the result obtained by Mundo et al Indeed, patients with rapid cycling may be over-represented among AIM(+) patients and under-represented among AIM(À) patients. Mundo et al only evaluated the presence of rapid cycling in the previous 12 months, whereas we considered the lifetime history of rapid cycling.…”
Section: -Htt Gene and Antidepressant-induced Maniasupporting
confidence: 61%
“…According with clinical observations [46] D'Aquila et al [47,48] recently reported that the supersensitivity of dopamine receptors induced by antidepressants is followed, after 4 wk of imipramine discontinuation, by a reduced sensitivity of these receptors and a behavioural syndrome that mimics depression in humans. Antidepressant induced manic episodes in humans [38,41,49,50] and dopamine receptor sensitization should be considered not a mere iatrogenic phenomenon but the intensification of a spontaneous underlying hypomanic process.…”
Section: Antidepressants Induce a "Bipolar-like" Behaviormentioning
confidence: 99%
“…There is no good data to support this assumption [3]. A further controversy was raised by the assumption that tricyclic antidepressants would increase the recurrence rate and therefore deteriorate the course [4]. When analyzing this question one has to bear in mind that in untreated cases the cycle length is also shortening with increasing number of episodes.…”
Section: Introductionmentioning
confidence: 99%